Oleoylethanolamide supplementation in obese patients newly diagnosed with non-alcoholic fatty liver disease: Effects on metabolic parameters, anthropometric indices, and expression of PPAR-α, UCP1, and UCP2 genes. (June 2020) - Tutunchi, Helda; Ostadrahimi, Alireza; Saghafi-Asl, Maryam; Hosseinzadeh-Attar, Mohammad-Javad; Shakeri, Abolhasan; Asghari-Jafarabadi, Mohammad; Roshanravan, Neda; Farrin, Nazila; Naemi, Mohammad; Hasankhani, Milad
Graphical abstract: Abstract: The effects of oleoylethanolamide (OEA) on NAFLD are yet to be examined in human. The objective of the present study was to examine the effects of OEA supplementation along with weight loss intervention on the expression of PPAR-α, uncoupling proteins 1and 2 (UCP1 and UCP2) genes in the peripheral blood mononuclear cells (PBMCs), metabolic parameters, and anthropometric indices among obese patients with NAFLD. In this triple-blind placebo-controlled randomized clinical trial, 76 obese patients newly diagnosed with NAFLD were randomly allocated into either OEA or placebo group along with calorie-restricted diets for 12 weeks. At pre-and post-intervention phase, mRNA expression levels of PPAR-α, UCP1, and UCP2 genes in the PBMCs, serum levels of metabolic parameters as well as diet and appetite sensations were assessed. There was a significant increase in the expression levels of PPAR-α, UCP1, and UCP2 genes in the PBMCs, compared to the placebo at the endpoint. A significant decrease in the anthropometric indices, energy and carbohydrate intakes, glycemic parameters, except for hemoglobin A1c concentration was also observed in the OEA group, compared to the placebo group. OEA treatment significantly resulted in decreased serum levels of triglyceride (TG), alanine aminotransferase (ALT), aspartate aminotransferase (AST), ALT/AST, increased serum levels of high-density lipoprotein cholesterol (HDL-C), and improved appetite sensations. Importantly, a significant improvement in TG, ALT, AST, ALT/AST, HDL-C levels as well as appetite sensations by OEA were under the influence of body mass index (BMI). Although liver steatosis severity was significantly reduced in both groups, the between-group differences did not reach statistical significance ( P = 0.061). In conclusion, the present study, for the first time, revealed that OEA supplementation significantly improved anthropometric and metabolic risk factors related to NAFLD.